Evaluasi Kinerja Operasional dan Strategi Manajemen Pemeliharaan Mesin Extruder Berbasis OEE : Studi Kasus pada PT Glora Industri Nusantara - Hotman Vincent Siregar; Fetty Nurlia Muzayanah (Journal of Management and Creative Business, 2026)
This study evaluates the operational performance of the Single Screw Extruder Line I machine at PT Glora Industri Nusantara, a plastic hose manufacturing company experiencing unplanned downtime and production fluctuations that affect productivity and profitability. The study aims to measure machine effectiveness using the Overall Equipment Effectiveness (OEE) method and identify dominant loss factors through Six Big Losses analysis and Pareto Diagram mapping. A quantitative approach with a descriptive case study design was applied using secondary data from production logsheets and maintenance history cards collected during a 12-week observation period from October to December 2025. The findings show that the average OEE value of the machine is 75.27%, below the world-class standard of 85%. Reduced speed losses (27.84%) and equipment failure (27.25%) were identified as the main contributors to inefficiency. The lowest OEE occurred in Week 5, reaching 52.67% due to a compressor system breakdown that affected production capacity and order fulfillment. This study provides recommendations for improving preventive maintenance strategies, establishing operational speed standards, and managing critical spare parts to reduce downtime and improve machine performance.